Trends and coverage of strengthening literacy in biology learning: Systematic literature review of the Scopus database in four decades - Husamah, Husamah; Adlini, Miza Nina; Luzyawati, Lesy; Lestari, Nurdiyah (Universitas Islam Negeri Sumatera Utara, 2024)
This study aimed to analyze the trend and scope of strengthening literacy in biology learning over four decades that will make a valuable contribution to the biology learning in all educational levels. This study employed a systematic literature review (SLR) method adapted from the PRISMA model. This SLR obtained several interesting findings. It was found that the theme of biology and literacy reached its peak in 2023. We found two main countries to focus on, namely the United States and Indonesia. Biology and its learning are synonymous with scientific/science literacy. Other types of literacy that are widely promoted by researchers are information literacy, quantitative literacy, health literacy, visual literacy, computer literacy, three-dimensional literacy, reading literacy, media literacy, assessment literacy, epigenetic literacy, digital literacy, and environmental literacy. In the Indonesian context, we suggest that biology learning needs to be oriented towards strengthening the literacy aspects-science literacy, information literacy, quantitative literacy, health literacy, visual literacy, computer literacy, three-dimensional literacy, reading literacy, media literacy, assessment literacy, epigenetic literacy, digital literacy, and environmental literacy-found in SLR because each of them has an urgency.